Contribution à l’étude des Coléoptères et Hyménoptères dans le sud-est algérien (Cas d'Oued Souf) - ASSILA, Assia; AYA, Zohra; MEBARKI, Ikhlas; MEBARKI, Ouifa; LEBIHI, Smail (Université of Eloued, 2021)
We made a contribution to the study of coleoptera and hymenoptera in the south-east of Algeria (case of Oued-Souf). Our study is proposed as a contribution to the quantitative and qualitative knowledge of insects captured by several types of trapping in the south-eastern Algerian region in Oued Souf. The methods they used during the sampling periods (Barber pots, Reaper net, colorful traps), allow to capture the maximum of existing insects. The sampling makes it possible to list 263 insect individuals, distributed over 2 orders of coleoptera and hymenoptera. At the levels of palm grove of Robah station (traditional station), the census allowed to have 88 individuals distributed over 5 families and 11 species, and Hassani abdel karim Station (abandoned station) the census allowed to have 71 individuals distributed over 2 families and 6 species, and finally modern palm grove (hassi khalifa station) There are 104 individuals representing in 3 families and 9 species. The best presented families are Tenebrionidae with 15 species, followed by fornicidae with 4 species. Most of the determined families have a low abundance. Coleoptera with 22% of individuals The values of the Shannon-Weaver diversity index fluctuate between 3.1 bits for the palm grove of the Robah station and 2.52 bits at the level of the palm grove of the hassani abdel karim station on the one hand and on the other hand 2.72 bits have been noted for the hassi khlifa palm grove.
Biodiversité et Environnement
Keywords: Coleoptera; hymenoptera; palm grove; Robah; hassani abdel karim; hassi khlifa; Oued-Souf.; غمديات-الأجنحة ، غشائيات